A new species of Japanese oribatid mite, Zachvatkinibates erimo sp. nov., showing sexual dimorphism (Acariformes: Oribatida: Punctoribatidae) - Shimano, Satoshi; Aoki, Jun-Ichi (Zootaxa, 2019)
A new species of oribatid mite, Zachvatkinibates erimo sp. nov., is described from a sandy beach in Hokkaido, North Japan. The new species exhibits a clear sexual dimorphism, showing enlarged areae porosae on the notogaster of the male. A key is provided to sexually dimorphic species of Zachvatkinibates.